Telemodernities television and transforming lives in Asia - Lewis, Tania; Martin, Fran 1971-; Sun, Wanning 1963- (Duke University Press, 2016)
Tania Lewis, Fran Martin, and Wanning Sun analyze the complex social and cultural significance of lifestyle television programming in China, India, Taiwan, and Singapore, showing how it adds insight into late Asian modernity, media cultures, and broad shifts in the nature of private life, identity, citizenship, and social engagement
Description based on publisher supplied metadata and other sources
Keywords: Reality television programs - Taiwan; Lebensstil -- Motiv; Reality-TV; Indien; China; Taiwan